Preparation and characterization of low-yellowing cross-linked shell microencapsulated phase change materials for latent thermal energy storage. (15th August 2022) - Lu, Shaofeng; Zhang, Manyan; Shi, Wenzhao; Zhao, Zhe; Królczyk, Grzegorz; Li, Zhixiong
Abstract: A Cross-linked microencapsulated phase change material (MEPCM) was prepared using butyl stearate as the core material and isophorone diisocyanate (IPDI) and triethanolamine (TEA) as the reaction monomers, while a Linear MEPCM was prepared using 2, 4-toluene diisocyanate (TDI) and diethylenetriamine (DETA) as the reaction monomers. The thermal stability, densification, chemical structure, phase change properties and surface morphology of the two types of microcapsules were characterized and analyzed, respectively, and the thermal storage properties and whiteness of the finished fabrics with the two microcapsules were measured. The results showed that the surface of the prepared Cross-linked MEPCMs was smooth and dense, with good wrapping effect and no leakage of core material, while the Linear microcapsules had serious leakage of core material and adhesion between particles; the thermal stability and denseness of the cross-linked microcapsules were significantly improved compared with the linear-shell microcapsules. After continuous drying at 120 °C for 6 h, the mass loss rate of cross-linked microcapsules was only 6.23%, while the mass loss rate of the linear microcapsules was up to 22.35%. The fabric finished with the cross-linked microcapsules had a great phase change properties and wash resistance, the whiteness was significantly higher than that of the linear microcapsules, had an obvious low yellowing characteristic. The prepared microcapsules had good prospects for textile applications. Highlights: A novel low-yellowing cross-linked shell microencapsulated PCM is proposed Thermal stability and denseness of the cross-linked microcapsules is significantly improved Mass loss rate of the cross-linked microcapsules is as low as 6.23%